GnRH Antagonist/Letrozole Versus Microdose GnRH Agonist Flare Protocol in Poor Responders Undergoing In Vitro Fertilization - Robab Davar; Homa Oskouian; Shahnaz Ahmadi; Razieh Dehghani Firouzabadi (Elsevier, 2010)
Objective: To evaluate and compare the efficacy of microdose gonadotropin-releasing hormone (GnRH) agonist flare (MF) and GnRH antagonist/letrozole protocols in poor responders undergoing in vitro fertilization. Materials and Methods: A total of 94 poorly responding patients were randomized in an ovarian stimulation protocol with a MF, or a letrozole and high dose follicle-stimulating hormone/human menopausal gonadotropin and flexible GnRH antagonist protocol. Results: There was no significant difference in mean age, body mass index, basal serum follicle stimulating hormone and estradiol levels, duration of infertility, distribution of etiology of infertility, and the number of previously failed in vitro fertilization cycles. The days of stimulation, mean gonadotropin dose, the number of mature follicles, and oocytes retrieved and metaphase II oocytes retrieved, serum estradiol level on the day of human chorionic gonadotropin administration, and the percentage of top and good quality embryos were significantly higher in the MF group. The endometrial thickness, fertilization rate, and the number of embryos transferred were similar in both groups. The implantation and clinical pregnancy rates were higher in the MF group and the total cancellation rate was higher in the GnRH antagonist/letrozole group, but these findings were not statistically significant. Conclusion: The addition of letrozole to the GnRH antagonist for poor responders does not improve the outcome of assisted reproductive technology cycles. The MF protocol remains the most appropriate protocol in poor responders.